A facile strategy based on the metal-free design of carbon to deliver an insight into the active sites for liquid phase carbocatalysis. Issue 26 (4th March 2020) - Wu, Shuchang; Pan, Xiaoli; Xu, Shutao; Lin, Yangming; Yan, Hua; Wen, Guodong; Diao, Jiangyong; Liu, Hongyang
Abstract : An effective approach based on the metal-free design of a carbon catalyst was developed to study the active sites for some carbon catalyzed reactions. Abstract : An effective method to study the active sites for carbocatalysis is proposed based on designing a carbon catalyst in the absence of metal as the growth catalyst. The results suggest that the oxygenated groups on the aromatic carbons are mainly responsible for the catalytic reduction of nitrobenzene and some other reactions.